2012
DOI: 10.1002/anie.201204047
|View full text |Cite
|
Sign up to set email alerts
|

Alkynoate Synthesis through the Vinylogous Reactivity of Rhodium(II) Carbenoids

Abstract: A new rhodium carbenoid approach to access alkynoates has been developed. This transformation combines the addition of enol ethers at the vinylogous position of β-siloxy-substituted vinyldiazo derivatives and an unprecedented siloxy group migration to yield the products as single diastereomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…5 Other factors found to favor vinylogous reactivity were electron deficient dirhodium catalysts, polar solvents, and bulky esters on the carbenoid. Recently, we 6 and others 7 have studied this unusual vinylogous reactivity in a variety of transformations, using a combination of experimental and theoretical studies to gain a better understanding of this chemistry. 8 We have found that dimolybdenum, diruthenium and especially silver catalysts enhance vinylogous reactivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Other factors found to favor vinylogous reactivity were electron deficient dirhodium catalysts, polar solvents, and bulky esters on the carbenoid. Recently, we 6 and others 7 have studied this unusual vinylogous reactivity in a variety of transformations, using a combination of experimental and theoretical studies to gain a better understanding of this chemistry. 8 We have found that dimolybdenum, diruthenium and especially silver catalysts enhance vinylogous reactivity.…”
mentioning
confidence: 99%
“…8 We have found that dimolybdenum, diruthenium and especially silver catalysts enhance vinylogous reactivity. 6a-c Another major breakthrough was the discovery that chiral bulky dirhodium catalysts could enhance vinylogous reactivity, especially if the trapping nucleophile is also sterically demanding. 6d …”
mentioning
confidence: 99%
“…3 Traditional approaches for the synthesis of γ-fluoro-α,β-unsaturated carbonyls mainly rely on electrophilic fluorination of conjugated enol ethers 4 and Wittig-type reaction of α-fluoro aldehydes or ketones. 5 Recently, we 6 and others 7 have described that metal-stablized vinylcarbenes derived from vinyldiazoacetates can selectively display electrophilic reactivity at the vinylogous position instead of the carbene site. This type of behavior is especially favorable when silver catalysts are used.…”
mentioning
confidence: 99%
“…This type of behavior is especially favorable when silver catalysts are used. 6c,6d,7h In this communication, we report a silver-catalyzed vinylogous fluorination to generate highly functionalized γ-fluoro-α,β-unsaturated carbonyls (eq. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation